Asimilasi Nilai-nilai Islam dalam Tradisi Tedhak Siten di Menganto Prespektif Komunikasi Budaya Robert E. Park - Zahra, Upi; Saepullah, Saepullah; Izzah, Lailatul (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This research aims to analyze the process of cultural assimilation between Islamic values and the Tedhak Siten tradition in Menganto, Mojowarno, Central Java. The research method uses a qualitative descriptive approach, involving key figures in the tradition, including religious leaders and community figures selected through purposive sampling. Data was collected through in-depth interviews, participatory observation, and documentation, and then analyzed using Robert E. Park's cultural communication theory. The results show that cultural assimilation occurs gradually through symbolic changes and spiritual meaning, such as replacing traditional mantras with Islamic prayers and reinterpreting main symbols, while maintaining local cultural identity. The entire process involves active participation across generations, with religious leaders playing a significant role in building legitimacy and acceptance of new ritual meanings. In conclusion, the Tedhak Siten tradition in Menganto serves as a model of harmonious cultural-religious integration, strengthening social cohesion, and ensuring the preservation of local traditions amidst modernization dynamics. This finding contributes to the development of multicultural communication studies, religious-cultural integration, and strategies for preserving traditions based on intergenerational dialogue.